Real Time Three‐Dimensional Echocardiographic Evaluations of Fetal Left Ventricular Stroke Volume, Mass, and Myocardial Strain: In Vitro and In Vivo Experimental Study. Issue 11 (11th April 2015) - Zhu, Meihua; Ashraf, Muhammad; Zhang, Zhijun; Streiff, Cole; Shimada, Eriko; Kimura, Sumito; Schaller, Traci; Song, Xubo; Sahn, David J.
Abstract : Background: Left ventricular stroke volume, mass, and myocardial strain are valuable indicators of fetal heart function. This study investigated the feasibility of nongated real time three‐dimensional echocardiography (RT3DE) to determine fetal stroke volume (SV), left ventricular mass (LVM), and myocardial strain under different conditions. Methods: To evaluate fetal hearts, fetal‐sized rabbit hearts were used in this study. The in vitro portion of this study was carried out using a balloon inserted into the LV of eight fresh rabbit hearts and driven by a calibrated pulsatile pump. RT3DE volumes were obtained at various pump‐set SVs. The in vivo experiments in this study were performed on open‐chest rabbits. RT3DE volumes were acquired at the following conditions: baseline, simulated hypervolemia, inferior vena cava (IVC) ligation, and ascending aorta (AAO) ligation. Displacement values and sonomicrometry data were used as references for RT3DE‐derived SV, LVM, longitudinal strain (LS), and circumferential strain (CS). Results: Excellent correlations between RT3DE‐derived values and reference values were demonstrated and accompanied by high coefficients of determination ( R 2 ) for both in vitro and in vivo studies for SV, LVM, LS, and CS (in vitro: SV: R 2 = 0.98; LVM: R 2 = 0.97; LS: R 2 = 0.87, CS: R 2 = 0.80; in vivo: SV: R 2 = 0.92; LVM : R 2 = 0.98; LS: in vivo: R 2 = 0.84; CS: in vivo: R 2 = 0.76; all P < 0.05). Conclusions: RT3DE is capable of quantifying the SV, LVM, and myocardial strain of fetal‐sized hearts under different conditions. This nongated RT3DE may aid the evaluation of fetal cardiac function, providing a superior understanding of the progress of fetal heart disorders.